STATUS HUKUM ANAK HASIL PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN MALAYSIA - Wahida, Lia Nisa; Nurtanti, Eka Era; Dewi, Listyowati; Hidayah, Nurul; Aydina, Siti; Ardhana, Gita Jemima (Cahaya Ilmu Bangsa, 2024)
A marriage between two people with different nationalities or a mixed marriage can have legal consequences for children. Because the principles of citizenship in each country adhere to different principles, namely some adhere to the principles of jus sanguinis and jus soli, this gives rise to legal problems that result in children being able to have dual citizenship (bipatride) or no citizenship (apatride) before the child finally has to choose. one of citizenship when he/she is legally competent according to the applicable laws and regulations. The method used in this research is normative juridical research using primary legal sources and secondary legal sources. This research will discuss important points, namely the citizenship status of children before and after becoming legally competent and the rights they will obtain according to law in Indonesia and Malaysia. The citizenship rights of children for Malaysia are regulated in the Malaysian Constitution, where Malaysia adheres to or upholds the principle of Ius Sanguinis. Meanwhile, in Indonesia currently applies